Raton Elks celebrate 75th anniversary (Raton Range Raton, New Mexico, 1978)
Newspaper article the 75th anniversary of the Raton Elks Club.
Master List item # 10
File location is in the Raton File Cabinet
Keywords: Leahy, Jerry; Morrow, John; Elliott, Eugene; Vigil, F.A. (Tony); Crawford, W.P.; Wilmer, Joe N; Sweeney, C.B.; Alarid, Ike; Elks Club; La Mesa Park; Local History; Biography; Life and Customs; Anniversary; Celebration; Raton, New Mexico; Las Cruces, New Mexico; Albuquerque, New Mexico; Santa Fe, New Mexico